2021
DOI: 10.1007/s40475-021-00248-z
|View full text |Cite
|
Sign up to set email alerts
|

Giardia duodenalis Virulence — “To Be, or Not To Be”

Abstract: Purpose of review Here, we review recent progress made on the genetic characterization of Giardia duodenalis assemblages and their relationship with virulence. We also discuss the implications of virulence factors in the pathogenesis of giardiasis, and advances in the development of vaccines and drugs based on knowledge of virulence markers. Recent findings The use of transcriptomic and proteomic technologies as well as whole genome sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 88 publications
(79 reference statements)
1
19
0
Order By: Relevance
“…Contact-independent mechanisms also have shown to contribute to the degradation of the TJ proteins and compromised intestinal integrity following Giardia infections; Giardia trophozoites contain a plethora of secreted molecules, including cysteine proteases (CPs), capable of degrading multiple components of the host immune system (60)(61)(62). The CPs secreted by Giardia trophozoites are considered emerging virulence factors that are able to degrade TJ proteins (i.e., claudin-1 and -4, occludin, E-cadherin) in IECs and are also capable of degrading chemokines expressed by parasitized IECs (63,64).…”
Section: Giardia Disrupts Tight Junction Proteins and Modulates Intes...mentioning
confidence: 99%
See 2 more Smart Citations
“…Contact-independent mechanisms also have shown to contribute to the degradation of the TJ proteins and compromised intestinal integrity following Giardia infections; Giardia trophozoites contain a plethora of secreted molecules, including cysteine proteases (CPs), capable of degrading multiple components of the host immune system (60)(61)(62). The CPs secreted by Giardia trophozoites are considered emerging virulence factors that are able to degrade TJ proteins (i.e., claudin-1 and -4, occludin, E-cadherin) in IECs and are also capable of degrading chemokines expressed by parasitized IECs (63,64).…”
Section: Giardia Disrupts Tight Junction Proteins and Modulates Intes...mentioning
confidence: 99%
“…Notably, G. duodenalis trophozoites expressing a variant surface protein, VSP9B10A, were able to induce the loss of cell-cell contact and cell detachment at the sites of the trophozoites attachment (65). The incubation of IEC-6 cell monolayers with conditioned medium obtained from G. duodenalis trophozoites expressing VSP9B10A/IEC-6 cell monolayers co-culture also induced cytotoxicity, whereas the monoclonal antibody blockade targeting the VSP9B10A protein expressed by trophozoites reversed those cytotoxic effects at the trophozoite/epithelial cell interface (62,65).…”
Section: Giardia Disrupts Tight Junction Proteins and Modulates Intes...mentioning
confidence: 99%
See 1 more Smart Citation
“…Typing approaches below the species level have shown that the species G. duodenalis comprises the assemblages A–H [ 20 , 21 , 22 ], of which the assemblages A and B are considered as zoonotic and of relevance for human disease [ 20 , 23 ]. Thereby, the identification of virulence factors for the discrimination of mere colonization and true infection is still an issue of ongoing research [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additional to susceptibility, genetic variation of the giardia complex diversity suggests the possible apparition of virulent strains due to host adaptation and co-evolution. Current estimates indicate that nearly 184 million people get affected annually ( Argüello-García and Ortega-Pierres, 2021 ; Duarte et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%